A symbolic derivation approach for redundancy analysis - Ferraro, Sebastián José (2002)
Redundancy analysis is an important stage in plant instrumentation design that consists of classifying the measurements so as to determine the redundant ones. In this work, we propose a new method based on the symbolic derivation of the equations that constitute the nonlinear steady-state model of the plant under study. The strategy succeeds in overcoming the limitations of existing techniques with respect to accuracy as well as model size and complexity. The approach is nonnumeric, thus allowing independence from the operating point. No linearization is required because the method works directly on the original model equations. Another advantage is that there is no need to solve for the observable variables. The prototype was implemented in Matlab, and its performance was assessed for several academic and industrial case studies with accurate results.